2018
DOI: 10.7150/thno.27428
|View full text |Cite
|
Sign up to set email alerts
|

CD28null pro-atherogenic CD4 T-cells explain the link between CMV infection and an increased risk of cardiovascular death

Abstract: An increased risk of cardiovascular death in Cytomegalovirus (CMV)-infected individuals remains unexplained, although it might partly result from the fact that CMV infection is closely associated with the accumulation of CD28null T-cells, in particular CD28null CD4 T-cells. These cells can directly damage endothelium and precipitate cardiovascular events. However, the current paradigm holds that the accumulation of CD28null T-cells is a normal consequence of aging, whereas the link between these T-cell populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 46 publications
2
31
0
Order By: Relevance
“…In contrast, the effect of age on CD28 − CD4 and CD8 T cells is small. They concluded that the diminished expression of CD28 in T cells strongly suggests that these observations reflect CMV-associated immunomodulation rather than normal immunosenescence ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the effect of age on CD28 − CD4 and CD8 T cells is small. They concluded that the diminished expression of CD28 in T cells strongly suggests that these observations reflect CMV-associated immunomodulation rather than normal immunosenescence ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…The evidence from these studies has been used by some to support the hypothesis that an increase in the size of the CMV memory T cell population over time in humans is indicative of memory inflation. However, other studies have shown that large expansions in the frequency of CMV-specific memory T cells is a feature of being CMV positive irrespective of age, including studies of children as well as younger adults [51, 6367], this is also true when observing the absolute size of the memory T cell compartment [23, 52].…”
Section: Does Memory Inflation Of Cmv-specific T Cell Responses Occurmentioning
confidence: 99%
“…Expansions of these cells have long been associated with CMV infection, but the strength of the association between large numbers of these cells and CMV infection was grossly underestimated. Only in the presence of CMV infection do individuals exhibit cell numbers typically associated with clinical disease in the literature (usually several percent) 74 . A recent publication reported that treatment with ganciclovir in CMV + patients with anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis reduced the number of CD28 null CD4 T cells 75 .…”
Section: Cd28 Null Cd4 T Cells Are Strongly Associated With Cytomegalmentioning
confidence: 99%